A smooth approximation for non-linear second order boundary value problems using composite non-polynomial spline functions - CHAURASIA, Anju; GUPTA, Yogesh; SRIVASTAVA, Prakash C. (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
A different amalgamation of non-polynomial splines is used to find the approximate solution of linear and non-linear second order boundary value problems. Cubic spline functions are assembled with exponential and trigonometric functions to develop the different orders of numerical schemes. Free parameter k of the non-polynomial part is also used to form a new scheme, which elevates the accuracy of the solution. Numerical illustrations are given to validate the applicability and feasibility of the present methods and also depicted in the graphs. Mathematics Subject Classification (2010): 41A15, 65D07, 65D15, 65L10.